PENGARUH RETURN ON EQUITY DAN EARNING PER SHARE TERHADAP HARGA SAHAM PERUSAHAAN BAN PADA SEKTOR KOMPONEN DAN OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016 - ARIE FIRMANSYAH ARIE FIRMANSYAH (POLITEKNIK PIKSI GANESHA, 2019)
The goal for companies that have gone public is to maximize shareholder wealth through stock prices reflected in the capital market, high prices determined by low supply and demand. The thing that attracts a company's stock demand is one of them is the level of profit, if the company's profit capability is high then the demand for shares will rise and stock prices tend to increase. The problems that will be studied in this research is how the influence of the rate of return on capital and stock return per share on the tire company's stock price in the automotive sector and components listed on the Indonesia Stock Exchange. The sample in this research is tire company in automotive sector and components listed in Indonesian Stock Exchange for period that is 2007-2016 period with amount of company sample counted 3 company, overall amount of data analyzed is counted 30 data. Data collection method in this research is indirect method, that is secondary data of financial statement. Data analysis technique used is multiple linear regression analysis using Eviews software 5.0 . The results of this study show that simultaneously Return on Equity and Earnings per share have a significant influence on the stock price of 63.82% and the rest of 36.17% influenced by other factors not examined in this study. From the partial test the rate of return on equity and earnings per share gives a positive significant effect on Stock Price.